Management of Human Physiological Loads in Industrial Environments. : Manajemen Beban Fisiologis Manusia di Lingkungan Industri. - Habib, Razzokov (Universitas Muhammadiyah Sidoarjo, 2025)
This article presents the scientific and practical foundations for managing human physiological workloads in industrial settings. Based on ergonomic and human physiology theories, static and dynamic factors affecting workers’ physical states are analyzed. Modern methods, technical solutions, and management tools for preserving employee health and reducing fatigue in production processes are examined. The potential of innovative technologies—such as sensor monitoring, digital twins, and automation—to predict and manage workloads is critically assessed. The article concludes that effective management of physiological workloads in industrial enterprises is pivotal for enhancing economic efficiency, reducing occupational diseases, and ensuring long-term workforce sustainability. Highlights: Ergonomic & Physiological Analysis – Evaluates static and dynamic factors affecting workers' physical conditions. Technology-Driven Solutions – Assesses sensor monitoring, digital twins, and automation for workload management. Workforce Sustainability – Highlights the importance of reducing fatigue to enhance efficiency and long-term health. Keywords: Industrial Ergonomics, Workload Management, Workplace Safety, Fatigue Reduction, Occupational Health